Mengenal Toxic Habits Pada Anak Usia Remaja Di SMA Negeri 22 Kota Makassar - Sunarti, Sunarti; Ramli, Rahmawati; Suhermi, Suhermi; Bohari, Muh Ijlal Imam; AOLYA, ANDI RAHMADINA (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Toxic habits behavior is one of the mental disorders that often occur among adolescents, this is influenced by several factors including starting from family parenting patterns that tend to apply toxic parenting behavior in raising children. This service aims to increase adolescents' knowledge about toxic habits behavior, increase adolescents' motivation to participate in behavioral seminars both online and offline and reduce adolescents' habits in behaving toxic habits. This service uses the Health seminar method as a form of education to adolescents.The results of this service activity obtained an increase in knowledge of 95.1% of the 82 participants, an increase in adolescent motivation to participate in behavior seminars by 65.8% and adolescents promised to change their toxic habits behavior into the power to change themselves towards a more positive direction.It can be concluded that toxic habits behavior is certainly not good behavior so that this is expected to be changed towards a positive direction, for example making toxic habits behavior as self-motivation to change towards a positive direction. The way to change toxic behavior is through CERDIK (Regular health checks, get rid of cigarette smoke, diligent physical activity, balanced diet, adequate rest and manage stress). This making this CERDIK activity a positive Habits in everyday life.